(untitled) (The Journal of Plant Protection Sciences, 2020)
The experiment on utilization of botanicals in the management of the coconut perianth mite, Aceria guerreronis Keifer was conducted at Main Agricultural Research Station, Dharwad, Karnataka during 2003-04 with nine treatments. The results of the present study indicated that among different botanicals, NSKE 5 percent was found significantly superior in reducing the mite population with higher healthy nuts (81 nuts 4 bunches), least percentof damaged nut (65 per cent) and highest benefit which was on par with wettable sulphur. The next best treatmentwas neem oil 2 percent.